Preparation and property of duplex Ni–B–TiO2/Ni nano-composite coatings - Wang, S.J.; Wang, Y.; Shu, X.; Tay, S.L.; Gao, W.; Shakoor, R.A.; Kahraman, R. (World Scientific Publishing, 2015)
The duplex Nickel-Boron-Titania/Nickel (Ni-B-TiO2/Ni) coatings were deposited on mild steel by using two baths with Ni as the inner layer. TiO2 nanoparticles were incorporated into the Ni-B coatings as the outer layer by using solid particle mixing method. The microstructure, morphology and corrosion resistance of the duplex Ni-B-TiO2/Ni nanocomposite coatings were systemically investigated. The results show that the duplex interface was uniform and the adhesion between two layers was very good. The microhardness of duplex Ni-B-TiO2/Ni coating was much higher than the Ni coating due to the outer layer of Ni-B-TiO2 coating. The corrosion resistance of the duplex Ni-B-TiO2/Ni coating was also significantly improved comparing with single Ni-B coating. The Ni-B-10 g/L TiO2/Ni coating was found to have the best corrosion resistance among these duplex coatings. This type of duplex Ni-B-TiO2/Ni coating, with high hardness and good corrosion resistance properties, should be able to find broad applications under adverse environmental conditions.